EXPERIMENTAL STUDY ON THE USE OF STRAPPING BAND VARIATION AS A SUBSTITUTE FOR STEEL REINFORCEMENT IN THE MANUFACTURE OF PRECAST FOUNDATION FOR COASTAL CONSTRUCTION - Sitohang, Maria Septhree Winna; Elvira, Elvira; Supriyadi, Asep (Jurnal Teknik Sipil, 2023)
A solid foundation is a concrete mix using steel reinforcement, but the reinforcement has the disadvantage of being corrosive when used in coastal areas. Therefore, this research uses strapping bands as a substitute for steel reinforcement. This research is focused on the manufacture of mortar plates for lightweight construction, especially in foundation parts such as footing foundations.   This research used 5 (five) variations of slab mixture including, variation A1 which is mortar slab without additional strapping band, variation B1 which is mortar slab with additional 3 pieces of strapping band as thick as 1 layer on each top and bottom layer, so on up to variation B4 as thick as 4 layers. The results of the mortar plate bending test obtained the value of the bending moment of variations A1, B1, B2, B3, and B4 are 0.148 kN.m; 0.183 kN.m; 0.222 kN.m; 0.278 kN.m; 0.325 kN.m. Then the maximum bending moment value is averaged in the variation that uses a 4-layer thick strapping band. From this research it can be concluded that to get a high bending moment value, the more strapping bands are used.